Evaluation Study of Boundary and Depth of the Soil Structure for Geotechnical Site Investigation using MASW - Arisona, A.; Nawawi, Mohd; Khalil, Amin E.; Nuraddeen, U K; Hariri, Mohd; Fathi, M A (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
This study reviews the correlation between the experimental Rayleigh dispersion curve and the Vp & Vs ground model versus depth. Six samples of stations A , B , C , D ,  E  and  F  were used in the experiment.The geophone spacing used was set 1 m and total length of each line was 23 m. The result shows positive significance (best fit) of R2 that ranges from 0.80 to 0.90. The fk (frequency-wave number method) dispersion curves analysis confirmed that the soil structure investigated is divided into three zones: (1) Unsaturated soil zone (clay soil), in which the layer is dominated by soil with typically alluvial clayey silt and sand. The Vp ranges from 240 m/s to 255 m/s at a depth of 2 to 8 m. (2) The intermediate zone (stiff soil), in which the layer is dominated by sand, silt, clayey sand, sandy clay and clay of low plasticity. This structure is interpreted as partially saturated soil zone, the soil is typically very dense. It contains soft rock typically fill with cobble, sand, slight gravel and highly weathered at depth of 18 to 30 m with Vp of  255 to 300 m/s. (3) Saturated soil zone at a depth of  8 to 18 m with Vp of 300 to 390 m/s. There is a very good agreement between wave-number (k) and phase velocity (Vw)  produced. Both the two parameters shows similar pattern in the topsoil and subsurface layer, which constitute boundary field of soil structure. Moreover, relationship between phase velocity versus wave-length shows best fit of model from inversion with measured value (observed) in  implementation of the boundary and depth of each layer.